Preemergence Herbicides for Use in Ornamentals - Robert H. Stamps; Heidi M. Savage; Diane K. Rock; Jeffrey G. Norcini (EDIS)
Preemergence herbicides are herbicides that are applied prior to weed seed germination. Control of weeds using preemergence herbicides is most successful when the correct herbicide is applied in the correct manner to a weed-free growing medium prior to weed seed germination. This revised 60-page fact sheet was written by Robert H. Stamps, Heidi M. Savage, Diane K. Rock, and Jeffrey G. Norcini, and published by the UF Department of Environmental Horticulture, March 2012.